Elaboración de un plan estratégico de desarrollo para la empresa comercial la central, del cantón La Maná, provincia de Cotopaxi; periodo 2014-2018 - Esquivel Valencia, John Silver (2015)
This investigation has determined that it is necessary to realize of a diagnosis of the present situation of the company in relation to the knowledge of development plans; this information provided the necessary aspects to optimize the resource of a strategic direction, and also by structuring the SWOT profile. It has been obtained the base for the development of the principles, values and objectives’ company; the used methodology was based on the non-experimental design in order to analyze the real data, to determine recommendations, and to the design of the Strategic Development Plan. As a result, it was possible to show that the company needs proper guidance for taking decisions just because they have not provided the desired results....